Penanganan Dampak Pencemaran Udara Pada Jalan Utama Pembangunan Kawasan Industri Dan Permukiman Baru - Rusdi Alimaman; Medawati Medawati (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
In any new Industrial and settlement area it is necessary to carry out environmental assesment based on Environmental Impact Anlysis Study (EIA) which is stimulated in Goverment Ordinance (PP) number 27, 1999. In handling air pollution impact to pre-construction in sample industrial village of Serang and settlment city of Cimahi reffering the air pollution level exceeded maximum, hence it is categorized as negative not important. To condition know and after constructionn, handling air pollution in main road with to plaint Angsana (Pterocarpus indicus), Bougenvile (ougenvilea spectabilis) and Flamboyan (Delonix regia).